Generating brain-wide connectome using synthetic axonal morphologies - Remy Petkantchin; Adrien Berchet; Hanchuan Peng; Henry Markram; Lida Kanari (Nature Communications)
Abstract Recent experimental advancements, including electron microscopy reconstructions, have produced detailed connectivity data for local brain regions. On the other hand, for inter-regional connectivity, large-scale imaging techniques such as MRI are best suited to provide insights. However, understanding the relationship between local and long-range connectivity is essential for studying both healthy and pathological conditions of the brain. Leveraging a dataset of whole-brain axonal reconstructions, we present a technique to predict whole-brain connectivity at single cell level for pyramidal cells in the cortex by generating detailed whole-brain axonal morphologies from sparse experimental data. The computationally generated axons accurately reproduce the local and global morphological properties of experimental reconstructions. Furthermore, the computationally synthesized axons generate large-scale inter-regional connectivity, defining the projectome and the connectome of the brain, thereby enabling the in silico experimentation of large brain regions.